1999
DOI: 10.1097/00005537-199903000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of mast cell activity in the middle ears of children with otitis media with effusion

Abstract: Mast cells and its mediator tryptase, both indicators of a Th2-driven immune response, are present in a majority of ears that have chronic effusion. These findings support the hypothesis that middle ear mucosa is capable of an allergic response and that the inflammation within the middle ear of most OME patients is allergic in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…Kähonen and coworkers [18] demonstrated the presence of T helper and T suppressor cells in patients with otitis media, and this was confirmed in later studies [19,20]. We have recently shown the increased presence of mast cells in the middle ear of patients with atopy and OME [21]. Palva and coworkers [19] also noted the presence of, often degranulated, polymorphonuclear leukocytes in otitis media patients.…”
Section: Discussionsupporting
confidence: 64%
“…Kähonen and coworkers [18] demonstrated the presence of T helper and T suppressor cells in patients with otitis media, and this was confirmed in later studies [19,20]. We have recently shown the increased presence of mast cells in the middle ear of patients with atopy and OME [21]. Palva and coworkers [19] also noted the presence of, often degranulated, polymorphonuclear leukocytes in otitis media patients.…”
Section: Discussionsupporting
confidence: 64%
“…It is probably related to bacterial infection because bacteria can be cultured from up to 33% of middle ear effusions (MEE) in patients with OME [29,30]. In a second study by Hurst et al [31], tryptase and eosinophilic cationic protein (ECP) were found to be significantly elevated in the effusions of patients with OME versus control patients with eustachian-tube dysfunction. Whereas 87% of patients with OME were found to be atopic versus 40% of the controls, 95% of the patients with elevated tryptase were atopic.…”
Section: Otitis Mediamentioning
confidence: 99%
“…Some studies have found increased number of MCs and higher levels of histamine in adenoid, which may indicate that mast cells are the source of inflammatory mediators for Eustachian tube and middle ear [13][14][15]. Increased counts of MCs and elevated tryptase levels, in effusion and in middle ear mucosa, have been demonstrated in allergic patients with OME [16,17]. Clinical studies reporting high histamine levels in middle ear effusion in secretory otitis media [12,18] and in acute otitis [19], as well as experimental studies of guinea pigs in which histamine injection into the tympanic cavity had caused long-standing effusion [20], also point to histamine participation in the pathomechanism of middle ear inflammation.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 98%
“…MCs are more abundant in the epithelium than in the subepithelial layer, as compared to adenoid [12]. The role of mast cells and their mediators, such as tryptase and histamine, has been assessed in pathology of the middle ear mainly in adenoid hypertrophy and otitis media with effusion (OME) [13][14][15][16][17]. Some studies have found increased number of MCs and higher levels of histamine in adenoid, which may indicate that mast cells are the source of inflammatory mediators for Eustachian tube and middle ear [13][14][15].…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%